2009
DOI: 10.1345/aph.1m324
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Enterococcus faecium Endocarditis Treated with Combination Tigecycline and High-Dose Daptomycin

Abstract: Increasing doses of daptomycin may enhance efficacy without compromising safety, even in patients with some renal dysfunction. The combination of daptomycin and tigecycline may be useful for the treatment of multidrug-resistant E. faecium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 22 publications
(2 reference statements)
1
33
0
1
Order By: Relevance
“…Multiple other case reports describe daptomycin failures, some as a result of emergence of daptomycin-resistance during treatment. 210,211 Other investigators have suggested that higher doses of daptomycin (8-10 mg·kg…”
Section: Daptomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple other case reports describe daptomycin failures, some as a result of emergence of daptomycin-resistance during treatment. 210,211 Other investigators have suggested that higher doses of daptomycin (8-10 mg·kg…”
Section: Daptomycinmentioning
confidence: 99%
“…[211][212][213][214][215][216][217] A number of in vitro evaluations [214][215][216] suggested that ampicillin and ceftaroline in combination with daptomycin demonstrate the greatest synergistic activity compared with other β-lactam-daptomycin combinations.…”
Section: Daptomycinmentioning
confidence: 99%
“…Similar results were reproduced in other studies examining the efficacy of tigecycline in experimental enterococcal endocarditis both in rabbits (10) and in rats (14). Moreover, successful use of tigecycline combinations has been described for clinical enterococcal endocarditis (15,16). A possible explanation for the discrepancy between tigecycline's bacteriostatic nature and these promising data would be the low MICs of Gram-positive cocci that allow achievement of high AUC/MIC values.…”
supporting
confidence: 79%
“…Several reports have demonstrated effective use of daptomycin plus tigecycline for the treatment of endocarditis caused by E. faecium (44)(45)(46). In our hands, this combination was frequently antagonistic, but again, in vivo data are required to confirm this finding.…”
Section: Discussionmentioning
confidence: 53%